P-165 Which are the determining factors influencing the success rate of egg donation programs with imported vitrified oocytes?. (30th June 2022) - Donno, V; Greco, E; Greco, A; Miniasi, M.G; Pristerà, A; Pirastu, G; Varricchio, M.T; Litwicka, K; Arrivi, C; Mencacci, C; Greco, P
Abstract: Study question: Which are the determining factors influencing the success rate of egg donation programs with imported vitrified oocytes? Summary answer: Number of oocytes available after warming, male BMI and semen characteristics are critical parameters influencing reproductive results of oocyte donation programs with imported vitrified oocytes What is known already: The use of vitrified oocytes from foreign banks and the performance of ICSI using fresh sperm from the recipient's partner is a widely used method of heterologous fertilisation. Recent evidence has questioned the overall effectiveness of this approach: vitrification and warming may reduce the number of oocytes available for insemination, resulting in a lower rate of live births per cycle. Recent studies have attempted to define the right clinical strategy to improve the effectiveness of oocyte vitrification cycles, stressing the importance of the number of imported oocytes (8-9 oocytes) and transfer to the blastocyst stage. Study design, size, duration: Observational longitudinal cohort study of 431 cycles of oocyte donation conducted between January 2015 and February 2019. A total of 398 couples (mean female age: 43.2 ± 3.5, 28-50 years; mean male age: 44.7 ± 6.1, 28-73 years) underwent an IVF cycle with imported donated vitrified oocytes (mean donor age: 25.2 ± 3.5, 19-34 years). All consecutive oocyte donation cycles conducted at the centre for Reproductive Medicine of the European Hospital in Rome were included. Participants/materials, setting, methods: In order to assess which factors are associated with the various outcomes, uni-and multi-variable analyses were conducted. In the multivariable analyses, variables that showed a p value<0.1 in the univariable analyses were included in the final model. The results were presented as Odds Ratio (OR). The corresponding 95% Confidence Interval (95% CI) was also exposed. A p value <0.05 was considered statistically significant. All analyses were performed with STATA v16.1 statistical software. Main results and the role of chance: A univariate analysis was carried out showing that among the demographic characteristics studied, the only one that proved significantly able to influence the outcome of the pregnancy test was male BMI. In 49% of unsuccessful cycles, the male BMI was above 25 (p = 0.03). The correlation is confirmed when comparing cycle outcomes in couples with normal/underweight vs overweight/obese men (p = 0.03). The relationship between female or donor BMI and treatment outcome, however, was not statistically significant. The day on which embryo transfer is performed affects the outcome of the cycle: transferring on day 2 compared to day 5 reduces the probability of clinical pregnancy (ET in day 2= positive clinical pregnancy in 4/16 (25%); ET in day 3= 158/307 (51.4%); ET in day 5=40/67 (59.7%). The relationship between male BMI classes and sperm parameters was studied: the distribution of concentration is different in the 3 BMI groups (p = 0.011); in particular, obese men have a significantly lower concentration than normal-weight men (p = 0.006 after Bonferroni correction). There were no statistically significant differences in volume (P = 0.722), morphology (p = 0.100) and motility (p = 0.179), although there was a downward trend in motility, with a reduction in obese subjects compared to normal weight. Limitations, reasons for caution: This is an observational study and our findings are in contrast with previous studies which do not show any correlation between male partner BMI categories and reproductive outcomes in egg donation programs. Wider implications of the findings: Our study shows that the number of oocytes available after warming, male BMI, semen characteristics and blastocyst transfer are critical parameters able to influence the reproductive outcomes of egg donation programs with imported vitrified oocytes. Trial registration number: Not applicable